Observations of kinetic‐size magnetic holes in the magnetosheath. Issue 2 (23rd February 2017) - Yao, S. T.; Wang, X. G.; Shi, Q. Q.; Pitkänen, T.; Hamrin, M.; Yao, Z. H.; Li, Z. Y.; Ji, X. F.; De Spiegeleer, A.; Xiao, Y. C.; Tian, A. M.; Pu, Z. Y.; et al.
Abstract: Magnetic holes (MHs), with a scale much greater than ρi (proton gyroradius), have been widely reported in various regions of space plasmas. On the other hand, kinetic‐size magnetic holes (KSMHs), previously called small‐size magnetic holes, with a scale of the order of magnitude of or less than ρi have only been reported in the Earth's magnetospheric plasma sheet. In this study, we report such KSMHs in the magnetosheath whereby we use measurements from the Magnetospheric Multiscale mission, which provides three‐dimensional (3‐D) particle distribution measurements with a resolution much higher than previous missions. The MHs have been observed in a scale of 10–20 ρe (electron gyroradii) and lasted 0.1–0.3 s. Distinctive electron dynamics features are observed, while no substantial deviations in ion data are seen. It is found that at the 90° pitch angle, the flux of electrons with energy 34–66 eV decreased, while for electrons of energy 109–1024 eV increased inside the MHs. We also find the electron flow vortex perpendicular to the magnetic field, a feature self‐consistent with the magnetic depression. Moreover, the calculated current density is mainly contributed by the electron diamagnetic drift, and the electron vortex flow is the diamagnetic drift flow. The electron magnetohydrodynamics soliton is considered as a possible generation mechanism for the KSMHs with the scale size of 10–20 ρe . Key Points: Magnetosheath kinetic‐size magnetic holes are found with electron flow vortex caused by diamagnetic drift At the 90° pitch angle, the 34–66 eV electron flux decreased while 109–1024 eV electron flux increased inside the MHs Quasi‐2‐D EMHD soliton theory is applicable to the observations